Development of microencapsulated whey melon juice - ATHIRA SASIDHARAN ROOSHI M. K; Dr. Sudheer K. P (Guide); Er. Alfiya P. V (Co-guide) (Tavanur 2015 Kelappaji College of Agricultural Engineering and Technology)
Microencapsulation can be done by various methods viz; spray drying, spray chilling, fluidization, extrusion, and lyophilization. Among these methods, spray drying occupies importance in terms of the bland of the product, uniformity in coating core material with the wall material and continuity in production.
Development of microencapsulated whey melon juice